Boas práticas de reuso na autoria de objetos de aprendizagem - LIMA, Thacyla De Sousa (2019)
Learning Objects (LOs) are reusable digital resources tagged with metadata that can be used to support education. Reusability, as a way to improve the educational resources and to ease and speed up the authoring proccess, has been an important theme since the first research efforts on LOs. Indeed, there have been proposals on both LOs document and metadata formats and on authoring tools that allow customization and that support an authoring process for LOs. Therefore, this work aims to identify good reuse practices that improve OA authoring and to explore these good practices in the evolution of an authoring tool. For this, a systematic review of the literature was carried out. As a result of the review, we selected 47 articles that present a model to represent OAs or an authoring tool. In addition, some of the good practices identified were used to improve an authoring tool. The added functionalities were evaluated in an experiment with 11 teachers/tutors. The results showed that the good practices added improved and eased the authoring of LOs. By providing an overview of and what is still missing in the current approaches, this thesis is also useful to identify open research problems and paths to follow aiming at a better support for the reuse in the LO authoring processes.